2013
DOI: 10.1246/cl.130171
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Activation of Lipase by an Amino Acid with Alkyl–PEG Sulfate Ionic Liquid

Abstract: The synergetic effect of amino acids and an ionic liquid, 1-butyl-2,3-dimethylimidazolium ¡-cetylpolyoxyethylene(10) ether sulfate (IL1), as coating materials on lipase was discovered: coating on lipase PS using a certain amino acid with IL1 was found to be very effective for accelerating the lipase-catalyzed transesterification of secondary alcohols while maintaining perfect enantioselectivity.Lipases are among the most widely used enzymes applicable for various substrates; however, the reaction rate and enan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…17 Lipase PS was a remarkably suitable enzyme to give (2S,3R)-4-t-butyldimethylsilyloxy-2,3-epoxybutyl acetate (98% ee) from the corresponding racemic alcohol by enzymatic asymmetric acetylation with vinyl acetate. 18 In the present case with (±)-4 however, lipase PS coated with an ionic liquid [IL 1:a-cetylpolyoxyethylene (19)ether sulfate] 19 could not discriminate the enantiomers of 4, and after only 4 h at room temperature, (±)-4 furnished the corresponding racemic acetate (±)-6 in 95% yield (Scheme 2). The enzymatic route was therefore abandoned.…”
Section: 2mentioning
confidence: 60%
“…17 Lipase PS was a remarkably suitable enzyme to give (2S,3R)-4-t-butyldimethylsilyloxy-2,3-epoxybutyl acetate (98% ee) from the corresponding racemic alcohol by enzymatic asymmetric acetylation with vinyl acetate. 18 In the present case with (±)-4 however, lipase PS coated with an ionic liquid [IL 1:a-cetylpolyoxyethylene (19)ether sulfate] 19 could not discriminate the enantiomers of 4, and after only 4 h at room temperature, (±)-4 furnished the corresponding racemic acetate (±)-6 in 95% yield (Scheme 2). The enzymatic route was therefore abandoned.…”
Section: 2mentioning
confidence: 60%
“…[20] MALD-TOF Mass experiments suggested that IL1 binds with the enzyme protein; therefore, it was assumed that the modified activity of lipase might be due to flexibility or conformation change of the lipase protein caused by the IL1-binding. [21] Furthermore, it was established that imidazolium cation affected the enantioselectivity of the lipase; IL1-coated lipase PS gave better enantioselectivity than an IL2coated one. [20] Amino acids have been used as a stabilizer of an enzyme during the purification process: commercial lipase PS involves ca.…”
Section: Activation Of Lipase-catalysed Reaction In An Ionic Liquid Smentioning
confidence: 99%
“…They include the immobilization of enzymes on solid supporters [6][7][8][9][10][11][12] and the use of additives such as inorganic salts, [13][14][15][16][17] ionic liquids, [18][19][20][21][22] or surfactants. They include the immobilization of enzymes on solid supporters [6][7][8][9][10][11][12] and the use of additives such as inorganic salts, [13][14][15][16][17] ionic liquids, [18][19][20][21][22] or surfactants.…”
Section: Introductionmentioning
confidence: 99%